Результати дослідження процесу сухого очищення забрудненої вовни - Шевченко, І. А.; Лиходід, В. В.; Алієв, Е. Б.; Полюсов, В. В.; Shevchenko, Igor; Lykhodid, Viktor; Aliyev, Elchin; Polusov, Vasily (КНТУ, 2013)
Наведено основні результати експериментальних досліджень малогабаритної тріпальної машини МТ 001А-12 при сухому очищенні забрудненої вовни та відображено оптимальне поєднання факторів, які здебільшого впливають на її роботу. Отримано математичну модель, яка адекватно описує робочий процес сухого очищення забрудненої вовни. Визначено оптимальні значення конструктивно-технологічних параметрів запропонованої конструкції малогабаритної тріпальної машини. Отримані результати досліджень є основою для удосконалення робочих органів існуючих конструкцій малогабаритних тріпальних машин аналогічного призначення. The aim of the research is to improve the process of dry cleaning polluted оvine wool by improving the construction of compact scutching machine. Presented the main results of experimental studies of compact scutching machine TM-001A-12 for dry cleaning polluted оvine wool and displayed an optimum combination of factors that primarily affect its work. A mathematical model that adequately describes the working process of dry cleaning polluted wool is obtained. Еxperimentally determined оptimum values of design and technological parameters of the proposed design of compact scutching machine with minimum energy costs for the implementation of working process. Experimentally set that the proposed design of the product performs stable technological process and provides degree of purification of polluted wool from 43,1 to 56,3%, which meets the requirements for this type scutching machine (at least 40%). The obtained results of research are the basis for the improvement of the working bodies of existing designs scutching machines similar purpose.
The results of studies of the process of dry cleaning polluted wool
Keywords: вівчарство; вовна; забрудненість; розпушування; тріпання; малогабаритна тріпальна машина; sheep breeding; wool; pollution; fluffing up; scutching; compact scutching machine